Study protocol of a mixed-methods study to develop and validate the Malaysian anti-hypertensive agents non-adherence scale in hypertensive patients - Yew, Sheng Qian; Mohd Nazan, Ahmad Iqmer Nashriq; Tan, Kit Aun (Universiti Putra Malaysia, 2022)
Introduction: Domains of adherence and non-adherence to hypertensive medications have not been extensively documented in Malaysia due to the absence of theoretically driven and culturally appropriate measurement tools, leading to a poor understanding of the adherence and underlying factors. We aim to identify these domains in Malaysian hypertensive patients and subsequently apply the findings to develop and validate the Malaysian Anti-Hypertensive Agents Non-Adherence Scale (MAANS). Methods: This study has an exploratory mixed-methods design. In Phase 1, we will recruit hypertensive patients from two health clinics to participate in a semi-structured interview. Recruitment of participants will terminate once thematic saturation is achieved. Coding and thematic analyses will be performed to identify the domains of adherence and non-adherence to anti-hypertensive medications. In Phase 2, based on the domains generated from Phase 1, we will develop the Malaysian Anti-Hypertensive Agents Non-Adherence Scale (MAANS). Four hundred hypertensive patients will be randomly selected. Data from 200 participants (serving as the calibration sample) will be subjected to exploratory factor analysis while data from additional 200 participants (serving as the validation sample) will be subjected to confirmatory factor analysis. Factor structure, predictive validity, and reliability of the MAANS will be statistically tested. Discussion: With the presence of the MAANS, health care providers can gather crucial information regarding barriers and facilitators to hypertensive treatment adherence and design effective health promotion programmes to reduce complications of uncontrolled hypertension.